Modified polyurethane adhesive for improving fiber / rubber bonding strength and preparation method thereof
The modified polyurethane adhesive is prepared by combining modified castor oil with isocyanate and other raw materials, which solves the problem of poor bonding of existing polyurethane adhesives and rubber, and significantly improves the interface bonding strength of fiber/rubber and the stability of the adhesive. .
Patent Information
- Application Number
- CN202411633422.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The poor bonding between existing polyurethane adhesives and rubber causes the fibers to fall off easily in the fiber/rubber composite materials, limiting the application of polyurethane adhesives.
Modified polyurethane is prepared by modifying castor oil, combined with isocyanate, chain extender, catalyst, acetone, pentaerythritol triacrylate, triethylamine and deionized water, and a modified polyurethane bond with good hydrophilicity and dispersion is prepared. agent.
The interface bonding strength between fiber and rubber is improved, the bonding between the adhesive and fiber/rubber is enhanced, and the stability and heat resistance of the adhesive are improved.
Smart Images

Figure CN119463790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a modified polyurethane adhesive for improving fiber / rubber bonding strength and a preparation method thereof. Background Art
[0002] Rubber products are widely used in all aspects of our modern life and industry, such as tires, conveyor belts, V-belts, etc. However, these rubber products need to be reinforced with fiber skeleton materials, otherwise it is difficult to ensure that the rubber products have sufficient strength. Due to the huge difference in modulus and polarity between the fiber and rubber materials, it is difficult to form a good interface layer between the fiber and the rubber matrix. Therefore, it is necessary to apply an adhesive to the fiber surface to form an interface layer between the fiber and the rubber.
[0003] Polyurethane adhesives have the advantages of being non-flammable, non-toxic, environmentally friendly, and easy to process, and therefore have been widely used. However, the existing polyurethane adhesives have poor bonding with rubber. When used in fiber / rubber composites, the fibers easily fall off the rubber matrix, which limits the use of polyurethane adhesives. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a modified polyurethane adhesive for improving the fiber / rubber bonding strength and a preparation method thereof.
[0005] The technical scheme of the present invention is: a modified polyurethane adhesive for improving the fiber / rubber bonding strength is prepared from the following raw materials in parts by weight: 10-20 parts of modified castor oil, 10-25 parts of isocyanate, 2-6 parts of chain extender, 0.2-0.4 parts of catalyst, 8-15 parts of acetone, 3-5 parts of pentaerythritol triacrylate, 5-10 parts of triethylamine and 30-40 parts of deionized water.
[0006] Description: The above adhesive is prepared by modifying castor oil to prepare modified polyurethane, so that the generated modified polyurethane has good hydrophilicity and dispersibility, can be effectively dispersed in deionized water, ensures that the adhesive layer is uniform, and the bonding between the adhesive and the fiber / rubber is good, which can effectively improve the interface bonding strength between the fiber and the rubber.
[0007] Furthermore, the preparation method of the modified castor oil comprises the following steps:
[0008] S1. Add sodium chloride and sodium silicate into distilled water and stir for 5 to 10 minutes to obtain a mixed solution, wherein the mass ratio of sodium chloride, sodium silicate and distilled water is 1:1.5 to 2.5:20 to 25;
[0009] S2, dividing castor oil into 2 equal parts, wherein 1 equal part of castor oil is put into a reaction container together with the mixed solution, and stirred for 20 to 30 minutes to obtain a mixed emulsion, wherein the mass ratio of the total mass of castor oil to the mixed solution is 1:0.2 to 0.3;
[0010] S3, under stirring, adding sulfuric acid solution to the mixed emulsion at 0-5°C, then heating the mixed emulsion, and keeping the temperature of the mixed emulsion once every 20-30°C increase, the keeping time is 30-45min, and adding sulfuric acid solution to the mixed emulsion during each keeping process until the temperature of the mixed emulsion reaches 65-70°C, adding another equal portion of castor oil, and keeping the temperature again for 30-40min to obtain a mixed solution, wherein the single addition amount of sulfuric acid solution accounts for 3-5% of the total mass of the mixed emulsion;
[0011] S4, shaking the mixed solution and then letting it stand until the oil phase and the water phase in the mixed solution are separated, then draining the water phase, and adjusting the pH of the oil phase to 6-8 with a sodium hydroxide solution to obtain modified castor oil.
[0012] Description: The castor oil has good emulsification properties after modification, and sodium silicate will react with sulfuric acid to generate nano-silicon dioxide particles, so that the final modified polyurethane adhesive has good stability and heat resistance, and the nano-silicon dioxide will be dispersed in the adhesive layer to improve the bonding strength between the fiber and rubber interface.
[0013] Furthermore, in step S3, the mass concentration of the sulfuric acid solution added initially is 75-85%, and the mass concentration of the sulfuric acid solution added each time thereafter is reduced by 5-8% compared with the previous addition.
[0014] Note: Gradually reducing the concentration of sulfuric acid solution can ensure that the mixed emulsion can fully react with the sulfide solution, control the reaction rate, avoid excessive reaction, and control the pH value of the mixed emulsion.
[0015] Furthermore, in step S4, the mass concentration of the sodium hydroxide solution is 15-20%.
[0016] Note: The sodium hydroxide solution of the above concentration has a good effect on adjusting the pH value, is easy to prepare, and is safe to use.
[0017] Furthermore, the isocyanate is a mixture of any one or more of diphenylmethane diisocyanate, isophorone diisocyanate, polymethylene polyphenyl polyisocyanate, trimethylhexane diisocyanate, and toluene diisocyanate in any ratio.
[0018] Description: The isocyanate in the above isocyanate can react with the hydroxyl group of castor oil to generate polyurethane, and the raw material cost is low and easy to obtain.
[0019] Furthermore, the chain extender is a mixture of any one or more of diaminobenzoic acid, dihydroxymethylacetic acid, dihydroxymethylpropionic acid, dihydroxymethylbutyric acid, and dihydroxymethylvaleric acid in any ratio.
[0020] Description: The above chain extender can increase the length of the polyurethane molecular chain, thereby increasing the strength and toughness of the polyurethane and improving the mechanical properties of the polyurethane adhesive.
[0021] Furthermore, the catalyst is a mixture of any one or more of dibutyltin dilaurate, N,N-dimethylethanolamine, and succinic acid in any ratio.
[0022] Description: The above catalyst can increase the reaction rate, reduce the reaction temperature, reduce the occurrence of side reactions, and improve the yield and quality of polyurethane.
[0023] On the other hand, the present invention provides a method for preparing a modified polyurethane adhesive for improving fiber / rubber bonding strength, which is used to prepare the modified polyurethane adhesive, comprising the following steps:
[0024] Step 1, place modified castor oil, isocyanate and chain extender into a flask, and stir for 15 to 20 minutes to obtain a reactant;
[0025] Step 2, keeping the reactant at 90-110° C., adding a catalyst to the reactant, reacting for 30-45 minutes, and adding acetone to the reactant during the reaction to dilute it, then reducing the insulation temperature of the reactant to 60-70° C., adding pentaerythritol triacrylate to continue the reaction for 1-2 hours, then reducing the insulation temperature of the reactant to 40-50° C., adding triethylamine to neutralize for 20-30 minutes, and obtaining an intermediate;
[0026] Step 3: adding deionized water into the intermediate and stirring at high speed for 30 to 40 minutes for emulsification to obtain a modified polyurethane adhesive.
[0027] Description: The above preparation method generates a modified polyurethane with good dispersibility by reacting modified castor oil with isocyanate, so that the modified polyurethane in the adhesive can be evenly dispersed, and nano-silicon dioxide particles are evenly dispersed in the adhesive, so that the adhesive can form a stable and uniform adhesive layer, thereby improving the bonding strength of the adhesive.
[0028] Furthermore, the stirring speed during the high-speed stirring is 500-600 r / min.
[0029] Note: Limiting the stirring speed can ensure the emulsification effect and ensure that the ingredients in the adhesive are evenly distributed.
[0030] The beneficial effects of the present invention are:
[0031] (1) The present invention prepares modified polyurethane by modifying castor oil, so that the generated modified polyurethane has good hydrophilicity and dispersibility, can be effectively dispersed in deionized water, ensures that the adhesive layer is uniform, and has good bonding between the adhesive and the fiber / rubber, which can effectively improve the interface bonding strength between the fiber and the rubber.
[0032] (2) The modified castor oil of the present invention has good emulsification properties, and sodium silicate reacts with sulfuric acid to generate nano-silicon dioxide particles, so that the modified polyurethane adhesive finally prepared has good stability and heat resistance, and the nano-silicon dioxide is dispersed in the adhesive layer to improve the bonding strength between the fiber and rubber interface.
[0033] (3) The preparation method of the present invention generates a modified polyurethane with good dispersibility by reacting modified castor oil with isocyanate, so that the modified polyurethane in the adhesive can be evenly dispersed. Nano-silicon dioxide particles are evenly dispersed in the adhesive, so that the adhesive can form a stable and uniform adhesive layer, thereby improving the bonding strength of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a line graph of the peel strength of each adhesive in Experimental Example 1 of the present invention;
[0035] Figure 2 is a line graph of the peel strength of each adhesive in Experimental Example 2 of the present invention;
[0036] Figure 3 is a line graph of the peel strength of each adhesive in Experimental Example 3 of the present invention;
[0037] Figure 4 is a line graph of the peel strength of each adhesive in Experimental Example 4 of the present invention;
[0038] Figure 5 It is a line graph of the peel strength of each adhesive in Experimental Example 5 of the present invention. DETAILED DESCRIPTION
[0039] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0040] Example 1: A modified polyurethane adhesive for improving fiber / rubber bonding strength is prepared from the following raw materials in parts by weight: 15 parts of modified castor oil, 18 parts of isocyanate, 4 parts of chain extender, 0.3 parts of catalyst, 11 parts of acetone, 4 parts of pentaerythritol triacrylate, 8 parts of triethylamine, and 35 parts of deionized water;
[0041] The preparation method of the modified castor oil comprises the following steps:
[0042] S1. Add sodium chloride and sodium silicate into distilled water and stir for 8 minutes to obtain a mixed solution, wherein the mass ratio of sodium chloride, sodium silicate and distilled water is 1:2:23;
[0043] S2, dividing castor oil into 2 equal parts, wherein 1 equal part of castor oil is put into a reaction container together with the mixed solution, and stirred for 25 minutes to obtain a mixed emulsion, wherein the mass ratio of the total mass of castor oil to the mixed solution is 1:0.25;
[0044] S3, under stirring, adding sulfuric acid solution to the mixed emulsion at 2°C, then heating the mixed emulsion, and keeping the temperature of the mixed emulsion once every 25°C, the keeping time is 38min, and adding sulfuric acid solution to the mixed emulsion during each keeping process until the temperature of the mixed emulsion reaches 68°C, adding another equal portion of castor oil, and keeping the temperature again for 35min to obtain a mixed solution, the single addition amount of sulfuric acid solution accounts for 4% of the total mass of the mixed emulsion; wherein, the mass concentration of the sulfuric acid solution added for the first time is 80%, and the mass concentration of the sulfuric acid solution added each time thereafter is reduced by 6% compared with the previous time;
[0045] S4, shaking the mixed solution and then standing it until the oil phase and the water phase in the mixed solution are separated, then discharging the water phase, and adjusting the pH of the oil phase to 7 using a sodium hydroxide solution with a mass concentration of 18%, thereby obtaining modified castor oil;
[0046] The isocyanate is isophorone diisocyanate, the chain extender is dimethylolbutyric acid, and the catalyst is dibutyltin dilaurate;
[0047] The preparation method of the modified polyurethane adhesive comprises the following steps:
[0048] Step 1, place modified castor oil, isocyanate and chain extender into a flask, stir for 18 minutes, and obtain a reactant;
[0049] Step 2, the reactant is kept at 100° C., and a catalyst is added to the reactant, and the reaction is continued for 38 minutes. During the reaction, acetone is added to the reactant to dilute it, and then the temperature of the reactant is reduced to 65° C., pentaerythritol triacrylate is added, and the reaction is continued for 1.5 hours, and then the temperature of the reactant is reduced to 45° C., and triethylamine is added to neutralize for 25 minutes to obtain an intermediate;
[0050] Step 3: adding deionized water into the intermediate and stirring at high speed for 35 minutes for emulsification to obtain a modified polyurethane adhesive; the stirring speed during high-speed stirring is 550 r / min.
[0051] Example 2: This example is basically the same as Example 1, except that the modified polyurethane adhesive is made of the following raw materials in parts by weight: 10 parts of modified castor oil, 10 parts of isocyanate, 2 parts of chain extender, 0.2 parts of catalyst, 8 parts of acetone, 3 parts of pentaerythritol triacrylate, 5 parts of triethylamine, and 30 parts of deionized water.
[0052] Example 3: This example is basically the same as Example 1, except that the modified polyurethane adhesive is made of the following raw materials in parts by weight: 20 parts of modified castor oil, 25 parts of isocyanate, 6 parts of chain extender, 0.4 parts of catalyst, 15 parts of acetone, 5 parts of pentaerythritol triacrylate, 10 parts of triethylamine, and 40 parts of deionized water.
[0053] Example 4: This example is basically the same as Example 1, except that the mass ratio of sodium chloride, sodium silicate and distilled water is 1:1.5:20.
[0054] Example 5: This example is basically the same as Example 1, except that the mass ratio of sodium chloride, sodium silicate and distilled water is 1:2.5:25.
[0055] Example 6: This example is substantially the same as Example 1, except that the mass ratio of the total mass of castor oil to the mass of the mixed solution is 1:0.2.
[0056] Example 7: This example is substantially the same as Example 1, except that the mass ratio of the total mass of castor oil to the mass of the mixed solution is 1:0.3.
[0057] Example 8: This example is basically the same as Example 1, except that the temperature of the mixed emulsion is kept warm every time it rises by 20°C.
[0058] Example 9: This example is basically the same as Example 1, except that the temperature of the mixed emulsion is kept warm every time it rises by 30°C.
[0059] Example 10: This example is substantially the same as Example 1, except that the temperature of the mixed emulsion reaches 65°C.
[0060] Example 11: This example is basically the same as Example 1, except that the temperature of the mixed emulsion reaches 70°C.
[0061] Example 12: This example is basically the same as Example 1, except that the mass concentration of the sulfuric acid solution initially added is 75%.
[0062] Example 13: This example is basically the same as Example 1, except that the mass concentration of the sulfuric acid solution initially added is 85%.
[0063] Example 14: This example is basically the same as Example 1, except that the mass concentration of the sulfuric acid solution added each time thereafter is reduced by 5% compared with the previous addition.
[0064] Example 15: This example is basically the same as Example 1, except that the mass concentration of the sulfuric acid solution added each time thereafter is reduced by 8% compared with the previous addition.
[0065] Example 16: This example is basically the same as Example 1, except that the reactants are kept warm at 90°C.
[0066] Example 17: This example is basically the same as Example 1, except that the reactants are kept warm at 110°C.
[0067] Example 18: This example is basically the same as Example 1, except that the insulation temperature of the reactants is subsequently lowered to 60°C, pentaerythritol triacrylate is added and the reaction is continued for 1.5 hours, and then the insulation temperature of the reactants is lowered to 40°C, and triethylamine is added for neutralization for 25 minutes.
[0068] Example 19: This example is basically the same as Example 1, except that the insulation temperature of the reactants is subsequently lowered to 70°C, pentaerythritol triacrylate is added and the reaction is continued for 1.5 hours, and then the insulation temperature of the reactants is lowered to 50°C, and triethylamine is added for neutralization for 25 minutes.
[0069] Comparative Example 1: Using Example 1 as a reference, a commercially available polyurethane adhesive was used.
[0070] Comparative Example 2: Using Example 1 as a reference, unmodified castor oil was used instead of modified castor oil.
[0071] Comparative Example 3: Taking Example 1 as a reference, unmodified castor oil was used instead of modified castor oil, and nano-silicon dioxide particles were additionally added to the prepared polyurethane adhesive.
[0072] Comparative Example 4: Taking Example 1 as a reference, the sulfuric acid solution was added to the mixed emulsion at one time before heating.
[0073] Comparative Example 5: Using Example 1 as a reference, the mass concentration of the sulfuric acid solution added each time thereafter does not change.
[0074] Comparative Example 6: Taking Example 1 as a reference, the insulation temperature of the reactants was maintained at 100°C without changing.
[0075] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the adhesive, the adhesive prepared in each embodiment is used to bond the rubber plate and the carbon fiber plate of the same area as the sample of each embodiment. After curing for 24 hours, the 180° peel strength test is performed on each sample. The specific exploration is as follows:
[0076] Experimental Example 1: Investigating the influence of raw material composition on adhesive performance
[0077] like Figure 1 As shown, by comparing Examples 1 to 3, it can be seen that the sample of Example 1 has the highest peel strength, indicating that the adhesive performance of Example 1 is the best and the raw material components selected in Example 1 are optimal;
[0078] By comparing Example 1 with Comparative Example 1: the peel strength of the sample in Example 1 is higher than that in Comparative Example 1, which indicates that the polyurethane adhesive of the present application has better bonding performance on the fiber / rubber interface than the commercially available polyurethane adhesive;
[0079] By comparing Example 1 with Comparative Examples 2 to 3: After using unmodified castor oil, the performance of the adhesive decreased. Although the use of added nano-silica particles can improve the performance of the adhesive, the improvement is not large. This may be because the polyurethane made from unmodified castor oil has poor dispersibility, resulting in the inability of the added nano-silica particles to be evenly distributed.
[0080] Experimental Example 2: Investigating the influence of the ratio of components of mixed solution and mixed emulsion on the performance of adhesive
[0081] like Figure 2 As shown, by comparing Example 1 and Examples 4 to 7, it can be seen that: if the ratio of sodium silicate to distilled water in the mixed solution is too high or too low, or if the ratio of the mixed solution in the mixed emulsion is too high or too low, both will lead to a decrease in the performance of the adhesive. Therefore, the component ratios of the mixed solution and the component ratios of the mixed emulsion selected in Example 1 are both optimal.
[0082] Experimental Example 3: Investigating the influence of thermal insulation parameters of mixed emulsion on adhesive performance
[0083] like Figure 3 As shown, by comparing Example 1 and Examples 8 to 11, it can be seen that: too high or too low insulation frequency in the mixed emulsion, too high or too low insulation terminal temperature, will lead to a decrease in adhesive performance, so the insulation parameters selected in Example 1 are optimal.
[0084] By comparing the example with comparative example 4, it can be seen that after the sulfuric acid solution was added once before heating, the performance of the adhesive decreased. This may be because the mixed emulsion could not react fully due to the one-time addition of the sulfuric acid solution.
[0085] Experimental Example 4: Investigating the effects of mass concentration and mass concentration variation of sulfuric acid solution on adhesive properties
[0086] like Figure 4 As shown, by comparing Example 1 and Examples 12 to 15, it can be seen that if the mass concentration of the sulfuric acid solution added to the mixed emulsion is too high or too low, or the mass concentration change is too high or too low, both will lead to a decrease in the performance of the adhesive. Therefore, the mass concentration and mass concentration change of the sulfuric acid solution selected in Example 1 are both optimal.
[0087] By comparing the embodiment with comparative example 5, it can be seen that when the mass concentration of the sulfuric acid solution does not change, the adhesive performance of the adhesive decreases. This may be because the mass concentration of the sulfuric acid solution does not change, causing the pH value of the mixed emulsion to decrease rapidly, affecting the generation of nano-silicon dioxide particles.
[0088] Experimental Example 5: Investigating the effects of the initial insulation temperature of the reactant and the insulation temperature variation parameters on the performance of the adhesive
[0089] like Figure 5 As shown, by comparing Example 1 and Examples 16 to 19, it can be seen that: if the initial insulation temperature of the reactant is too high or too low, or the temperature during each insulation is too high or too low, the performance of the adhesive will be reduced. Therefore, the initial insulation temperature and insulation temperature variation parameters selected in Example 1 are both optimal;
[0090] From the comparison between Example 1 and Comparative Example 6, it can be seen that after the temperature of the reactants is kept constant, the adhesive properties of the adhesive decrease. This may be because the reaction temperatures of the components in the reactants are different, and keeping the temperature constant will cause some components to fail to react fully.
Claims
1. A modified polyurethane adhesive for improving fiber / rubber bonding strength, characterized in that: The invention is prepared from the following raw materials in parts by weight: 10-20 parts of modified castor oil, 10-25 parts of isocyanate, 2-6 parts of chain extender, 0.2-0.4 parts of catalyst, 8-15 parts of acetone, 3-5 parts of pentaerythritol triacrylate, 5-10 parts of triethylamine and 30-40 parts of deionized water.
2. The modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 1, characterized in that: The preparation method of the modified castor oil comprises the following steps: S1. Add sodium chloride and sodium silicate into distilled water and stir for 5 to 10 minutes to obtain a mixed solution, wherein the mass ratio of sodium chloride, sodium silicate and distilled water is 1:1.5 to 2.5:20 to 25; S2, dividing castor oil into 2 equal parts, wherein 1 equal part of castor oil is put into a reaction container together with the mixed solution, and stirred for 20 to 30 minutes to obtain a mixed emulsion, wherein the mass ratio of the total mass of castor oil to the mixed solution is 1:0.2 to 0.3; S3, under stirring, adding sulfuric acid solution to the mixed emulsion at 0-5°C, then heating the mixed emulsion, and keeping the temperature of the mixed emulsion once every 20-30°C increase, the keeping time is 30-45min, and adding sulfuric acid solution to the mixed emulsion during each keeping process until the temperature of the mixed emulsion reaches 65-70°C, adding another equal portion of castor oil, and keeping the temperature again for 30-40min to obtain a mixed solution, wherein the single addition amount of sulfuric acid solution accounts for 3-5% of the total mass of the mixed emulsion; S4, shaking the mixed solution and then letting it stand until the oil phase and the water phase in the mixed solution are separated, then draining the water phase, and adjusting the pH of the oil phase to 6-8 with a sodium hydroxide solution to obtain modified castor oil.
3. The modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 2, characterized in that: In step S3, the mass concentration of the sulfuric acid solution added initially is 75-85%, and the mass concentration of the sulfuric acid solution added subsequently each time is reduced by 5-8% compared with the previous addition.
4. The modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 2, characterized in that: In step S4, the mass concentration of the sodium hydroxide solution is 15-20%.
5. The modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 1, characterized in that: The isocyanate is a mixture of any one or more of diphenylmethane diisocyanate, isophorone diisocyanate, polymethylene polyphenyl polyisocyanate, trimethylhexane diisocyanate and toluene diisocyanate in any ratio.
6. The modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 1, characterized in that: The chain extender is a mixture of any one or more of diaminobenzoic acid, dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutyric acid, and dimethylolvaleric acid in any ratio.
7. The modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 1, characterized in that: The catalyst is a mixture of any one or more of dibutyltin dilaurate, N,N-dimethylethanolamine and succinic acid in any ratio.
8. A method for preparing a modified polyurethane adhesive for improving fiber / rubber bonding strength, for preparing the modified polyurethane adhesive as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, place modified castor oil, isocyanate and chain extender into a flask, and stir for 15 to 20 minutes to obtain a reactant; Step 2, keeping the reactant at 90-110° C., adding a catalyst to the reactant, reacting for 30-45 minutes, and adding acetone to the reactant during the reaction to dilute it, then reducing the insulation temperature of the reactant to 60-70° C., adding pentaerythritol triacrylate to continue the reaction for 1-2 hours, then reducing the insulation temperature of the reactant to 40-50° C., adding triethylamine to neutralize for 20-30 minutes, and obtaining an intermediate; Step 3: Add deionized water into the intermediate and stir at high speed for 30 to 40 minutes for emulsification to obtain a modified polyurethane adhesive.
9. The method for preparing a modified polyurethane adhesive for improving fiber / rubber bonding strength according to claim 8, characterized in that: The stirring speed during the high-speed stirring is 500-600 r / min.